Uptake of low density lipoproteins by human leukemic cells in vivo: relation to plasma lipoprotein levels and possible relevance for selective chemotherapy. - Vitols, S (1990)
The success of cancer chemotherapy is dependent on the possibility to utilize biological differences between malignant and normal cells to selectively destroy the tumor cells. One such difference may be that of receptor-mediated cellular uptake of low density lipoproteins (LDLs). Previous studies have shown that leukemic cells from patients with acute myelogenous leukemia have elevated receptor-mediated uptake and degradation rates of plasma LDL in vitro compared to normal white blood and bone marrow cells, and that plasma cholesterol levels at diagnosis are inversely correlated with the LDL receptor activity of the malignant cells. An important question is whether the uptake of LDL by the leukemic cells is also increased in vivo. To evaluate the in vivo uptake of LDL, 11 adult patients with newly diagnosed acute myelogenous leukemia received an i.v. injection of [14C]-sucrose-labeled LDL. On degradation of [14C]sucrose-LDL, the radiolabeled sucrose moiety is known to remain trapped in the lysosomal compartment of the cells. After injection, radioactivity accumulated progressively for at least 12 hr in the leukemic cells. The uptake of radioactivity in vivo correlated with the rate of receptor-mediated degradation of 125I-labeled LDL by the leukemic cells assayed in vitro (r = +0.88, P less than 0.001). An inverse correlation between plasma LDL cholesterol concentrations and the in vivo cellular uptake of [14C]sucrose-LDL in whole blood (r = -0.76, P less than 0.01) indicates that the hypocholesterolemia is due to elevated LDL uptake by the leukemic cells. Postmortem biopsies from virtually all tissues were obtained from one patient, and the distribution of radioactivity revealed that the liver and bone marrow had accumulated most radioactivity; the adrenals had the highest uptake of label per gram of tissue weight. The results indicate that LDL may be used as a carrier targeting lipophilic cytotoxic drugs to leukemic cells.